Mendorong Partisipasi Aktif Masyarakat dalam Pengelolaan Sampah Melalui Kolaborasi Bank Sampah untuk Mewujudkan Smart City - Bunga Paramita; Rabena Aprilla; Aqilla Lajnah Panayitsa; Siti Maisarah; Syabina Febri Fitriana; Andre Khoirul Habibie; Asri Rendi Saputra (Pusat Riset dan Inovasi Nasional, 2025)
Population growth and lifestyle changes in Indonesia have led to complex waste management issues, negatively impacting social, health, and environmental sustainability aspects. To address this, a sustainable management approach that actively involves community participation is necessary. The concept of a Waste Bank, based on the 3R principles (Reduce, Reuse, Recycle), emerges as a strategic, community-based solution. This community service program aims to encourage active community participation in the Waste Bank program in Tanjung Uban Selatan, Bintan Regency, while supporting the realization of a Smart City based on intelligent and participatory environments. The methodology used is a qualitative approach to gain in-depth understanding. Primary data collection was carried out through interviews, participatory observations, and documentation studies. Key informants were purposively selected from various stakeholders, including Waste Bank administrators, local government representatives, and community members. The results show that, although initially challenging to increase community participation, the program has had a significant positive impact. It successfully shifted the community's view of waste as a valuable economic resource. Quantitatively, this is reflected in stable income from the sale of high-quality inorganic waste, such as metals and electronic waste. The program also led to strategic innovations, including sustainable education, waste savings incentives, social media use, and the